2004
DOI: 10.1111/j.1529-8817.2004.04100.x
|View full text |Cite
|
Sign up to set email alerts
|

STRUCTURAL CHARACTERIZATION OF THE TERMINAL DOMAINS OF LINEAR PLASMID‐LIKE DNA FROM THE GREEN ALGA ERNODESMIS (CHLOROPHYTA)1

Abstract: Terminal regions of linear plasmid-like DNA molecules from chloroplasts of the green alga Ernodesmis verticillata (Kützing) Børgesen were cloned and structurally characterized. Phosphorylation experiments with polynucleotide kinase indicated the presence of a 5 0 -phosphate, but the data did not reveal any protective protein(s) at the 5 0 end. To characterize the 3 0 end of these molecules, homopolymer-(poly(G)-) tailed molecules were annealed to and cloned into a linearized vector that was poly(C) tailed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…observations of abundant LMW DNA in chloroplasts of several species of Cladophorales 34 . The hairpin configuration of the plasmids derived from our sequence data corresponds with earlier data based on electron microscopy, endo-and exonuclease digestion experiments, acridine orange staining, and denaturing gel electrophoresis 34,37 . Fluorescence in situ hybridization, and Southern blot hybridisation indicated that these plasmids were present within the chloroplast only 35 , supporting the congruence between chloroplast 454 contigs and sequences from the LMW fraction ( Fig.…”
Section: A Prodigious Chloroplast Genome With Reduced Gene Setsupporting
confidence: 81%
See 1 more Smart Citation
“…observations of abundant LMW DNA in chloroplasts of several species of Cladophorales 34 . The hairpin configuration of the plasmids derived from our sequence data corresponds with earlier data based on electron microscopy, endo-and exonuclease digestion experiments, acridine orange staining, and denaturing gel electrophoresis 34,37 . Fluorescence in situ hybridization, and Southern blot hybridisation indicated that these plasmids were present within the chloroplast only 35 , supporting the congruence between chloroplast 454 contigs and sequences from the LMW fraction ( Fig.…”
Section: A Prodigious Chloroplast Genome With Reduced Gene Setsupporting
confidence: 81%
“…1d). Pioneering work revealed that these plasmids are singlestranded DNA (ssDNA) molecules of 1.5-3.0 kb that fold in a hairpin configuration and lack sequence similarity to the nuclear DNA 36,37 . Some of the hairpin plasmids contain putatively transcribed sequences with similarity to chloroplast genes encoding subunits of Photosystems I and II (psaB, psbB, psbC and psbF) 36 .…”
Section: Introductionmentioning
confidence: 99%
“…S3 ). Like dinoflagellates, this green algal order possesses an unusual plastid configuration that prevents amplification with standard plastid markers 33 . We found 5 OTUs in the Cladophorales and this is the first record of their occurrence in coral skeletons.…”
Section: Discussionmentioning
confidence: 99%
“…The chloroplast genomes of two other closely related orders, Cladophorales and Trentepohliales, have also not been sequenced or characterized in detail (but see La Claire et al. , , La Claire and Wang ). The Ulvales–Ulotrichales lineage, which is more distantly related in phylogenies of nuclear genes (Cocquyt et al.…”
Section: Discussionmentioning
confidence: 99%